PENEGAKAN HUKUM LINGKUNGAN HIDUP SERTA DINAMIKA PEMBAKARAN HUTAN DAN LAHAN DI INDONESIA - Baginda Parsaulian (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2019)
Forest fires are one of the environmental problems that often occur and are considered important so that they become local and global concerns. In Indonesia, forest and land fires (Karhutla) continue to occur, especially in Sumatra, Riau and Kalimantan. Great forest and land fires have occurred in Riau and Kalimantan in 1997-1998 with severe impacts, including health problems, land accidents, aircraft crashes and the effects of smoke reaching neighboring countries. The method of approach used in this study is juridical-normative, with the type of dogmatic research, a form of research on the relationship of law. The specification of this research is descriptive-analytical. The results of the discussion emphasized that law enforcement on environmental management is currently still difficult because of the difficulty in proving and determining the standard criteria for environmental damage.